(untitled) (London Journal of Medical and Health Research, 2025)
Olfactory Neuroblastoma (ON) A rare malignant tumor originating from the olfactory epithelium of the sinonasal tract, first described by Berger and Richard in 1924. Common symptoms patients typically present with unilateral nasal obstruction (70%), epistaxis (50%) and may also experience headaches, pain, excessive tearing, rhinorrhea, anosmia, and visual symptoms. Incidence Occurs at a rate of 0.1 per 100,000 in the pediatric population, making it particularly rare in toddlers. Imaging is crucial for staging the disease; both Computed Tomography (CT) and Magnetic Resonance Imaging (MRI) are used for diagnosis and assessment. Treatment Multimodal approach often recommended, including surgical resection, chemotherapy, and sometimes radiotherapy. The role of neoadjuvant chemotherapy in facilitating complete surgical resection requires further study. Prognosis Depends on the stage of the disease, including locoregional extension and presence of distant metastasis.